Pemberdayaan PKK Dusun Kepuh Pancarejo Melalui Diversifikasi Aksesori Fesyen dari Limbah Batik Hybrid - Resi Sepsilia Elvera; Triyanto Triyanto; Gina Eka Putri; Diah Indah Pratiwi; Melisa Herawati; Fikri Ardiansyah; Arjuna Dewanata Syahputra (SWARNA: Jurnal Pengabdian Kepada Masyarakat, 2026)
Economic growth in Gunungkidul Regency has slowed in recent years, affecting community welfare, particularly households that still depend on traditional sectors with low added value. This condition highlights the importance of community empowerment through strengthening productive skills capable of creating alternative sources of income. This community service program aimed to improve the skills and entrepreneurial capacity of PKK members in Kepuh Hamlet, Pancarejo, through the diversification of fashion accessory products made from hybrid batik fabric waste. The implementation methods included training, demonstrations, hands-on practice, and gradual mentoring in the design and production of marketable fashion accessories. The results showed an improvement in participants’ skills in processing hybrid batik fabric waste into economically valuable products, the creation of various fashion accessory products, and increased basic entrepreneurial understanding among PKK members. This program supports women’s empowerment and the development of sustainable culture-based creative industries. Therefore, this community service activity is important as a model of community empowerment based on creative skills that can sustainably support the improvement of household economies.